Bortezomib for autoimmune hemolytic anemia after intestinal transplantation. (12th March 2020) - Knops, Noël; Emonds, Marie‐Paule; Herman, Jean; Levtchenko, Elena; Mekahli, Djalila; Pirenne, Jacques; Van Geet, Chris; Dierickx, Daan
Abstract: AIHA is rare in the general population and associated with a mortality of 8%. In contrast, AIHA occurs in up to 12.2% of cases after intestinal transplantation and is associated with mortality up to 50%. Treatment entails a "step‐up" approach including corticosteroids, IvIg, plasmapheresis, and rituximab. However, AIHA after transplantation often is refractory to this strategy, contributing to a poor outcome. We describe a child with microvillous inclusion disease who developed AIHA 1 year after multivisceral transplantation that was refractory to standard therapy and was subsequently treated with bortezomib.We observed remission of AIHA within 1 week after the start of bortezomib. Bortezomib was associated with transient diarrhea, leucopenia, and elevated liver enzymes. Three years later, he remains in remission without important complications. Published data on bortezomib for autoimmune cytopenias outside SOT are discussed. This is the first report to support bortezomib as an important therapeutic alternative for AIHA after SOT. The occurrence and treatment of AIHA after SOT, and specifically intestinal transplantation, should be the subject of future registry studies to collect additional experience and explore the optimal therapeutic approach.